Perbedaan Penguasaan Pengelolaan Kelas Guru Matematika dan Kaitannya dengan Hasil Belajar Siswa Kelas XI SMA Negeri 2 Kotabaru - Hartini Hartini (STKIP Paris Barantai, 2019)
This research is a type of comparative study that is correlational in nature, which investigates the relationship of independent variables and dependent variable. This research aims to find out the learning outcomes of class II SMA Negeri 2 Kotabaru, student assessment of the level of mastery of classroom management and the difference in the level of mastery of the management of SMA Negeri 2 Kotabaru mathematics teacher class. The results of this study indicate that the mastery of the management of the class XI A mathematics teacher is better than the mastery of the management of the class XI B mathematics teacher. This is probably due to the different backgrounds of one teacher to another, such as age, length of office in the school that took place and what is more important is the professional level as teaching staff especially in basic teaching skills, namely classroom management skills. Mathematics learning results show that in class XI B is in the medium category. Whereas in class XI A is in the high category. So that it can be concluded that the mastery of mathematics teacher classroom management skills significantly has a positive effect on student learning outcomes. Keywords: Class Management, Mathematics Teachers, Learning Outcomes